3D bioprinting applications in neural tissue engineering for spinal cord injury repair - GÜNDÜZ, OĞUZHAN (ELSEVIER, 2020)
Spinal cord injury (SCI) is a disease of the central nervous system (CNS) that has not yet been treated successfully. In the United States, almost 450,000 people suffer from SCI. Despite the development of many clinical treatments, therapeutics are still at an early stage for a successful bridging of damaged nerve spaces and complete recovery of nerve functions. Biomimetic 3D scaffolds have been an effective option in repairing the damaged nervous system. 3D scaffolds allow improved host tissue engraftment and new tissue development by supplying physical support to ease cell function. Recently, 3D bioprinting techniques that may easily regulate the dimension and shape of the 3D tissue scaffold and are capable of producing scaffolds with cells have attracted attention. Production of biologically more complex microstructures can be achieved by using 3D bioprinting technology. Particularly in vitro modeling of CNS tissues for in vivo transplantation is critical in the treatment of SCI. Considering the potential impact of 3D bioprinting technology on neural studies, this review focus on 3D bioprinting methods, bio-inks, and cells widely used in neural tissue engineering and the latest technological applications of bioprinting of nerve tissues for the repair of SCI are discussed.
Keywords: Neural tissue engineering; 3D bioprinting; Scaffolds; Stem cells; Spinal cord injury; OLFACTORY ENSHEATHING CELLS; STEM-CELLS; BIODEGRADABLE POLYURETHANE; ELECTROSPUN NANOFIBERS; POLYETHYLENE-GLYCOL; HYALURONIC-ACID; SCAR FORMATION; SCAFFOLDS; HYDROGEL; DIFFERENTIATION